Evaluation Of Tax Incentive Policy For MSMEs In The Context Of National Economic Recovery At Tanjung Priok Small Tax Office In 2021 - Rulandari, Novianita; Sari, Mekar (Yayasan Sinergi Kawula Muda, 2023)
The purpose of this study was to evaluate the policy issued by the government regarding MSME Tax Incentives during the pandemic based on PMK Number 44 of 2020 at Tanjung Priok Small Tax Office Jakarta in the context of National Economic Recovery. The type of study used was a qualitative approach, where the researcher described the results of interviews and analyzed the data obtained in the field. This study was conducted from February to July 2022. The results of this study showed that the taxpayers enthusiastically welcome the policy issued by the government regarding MSME Tax Incentives. However, there are still taxpayers who do not know or have a lack understanding of the policies applied in their tax obligations on this tax incentive, therefore the taxpayers hope to get more detailed information and guidance for this policy